2016
DOI: 10.3389/fpsyg.2016.01235
|View full text |Cite
|
Sign up to set email alerts
|

Locality and Word Order in Active Dependency Formation in Bangla

Abstract: Research on filler-gap dependencies has revealed that there are constraints on possible gap sites, and that real-time sentence processing is sensitive to these constraints. This work has shown that comprehenders have preferences for potential gap sites, and immediately detect when these preferences are not met. However, neither the mechanisms that select preferred gap sites nor the mechanisms used to detect whether these preferences are met are well-understood. In this paper, we report on three experiments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
(125 reference statements)
0
6
0
Order By: Relevance
“…An important and robust finding in sentence processing is that comprehenders actively construct filler-gap dependencies (Fodor 1978;Crain & Fodor 1985;Stowe 1986;Traxler & Pickering 1996;Kaan et al 2000;Aoshima et al 2004;Phillips et al 2005;Chacón et al 2016), and that these processes appear to be suppressed in syntactic island configurations (Stowe 1986;Traxler & Pickering 1996;Phillips 2006;Yoshida et al 2014;Chacón 2015). These findings have been argued to reflect rapid deployment of fine-grained grammatical constraints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important and robust finding in sentence processing is that comprehenders actively construct filler-gap dependencies (Fodor 1978;Crain & Fodor 1985;Stowe 1986;Traxler & Pickering 1996;Kaan et al 2000;Aoshima et al 2004;Phillips et al 2005;Chacón et al 2016), and that these processes appear to be suppressed in syntactic island configurations (Stowe 1986;Traxler & Pickering 1996;Phillips 2006;Yoshida et al 2014;Chacón 2015). These findings have been argued to reflect rapid deployment of fine-grained grammatical constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that the gap site is constructed shortly after the filler is identified, a process called active dependency formation (Fodor 1978;Crain & Fodor 1985;Stowe 1986;Traxler & Pickering 1996;Kaan et al 2000;Aoshima et al 2004;Phillips et al 2005;Omaki et al 2015;Chacón et al 2016, see Pablos 2008 for review). For instance, Stowe (1986) found that reading times increased at the object us in (2) compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wealth of cross-methodological evidence that comprehenders actively construct filler-gap dependencies: electrophysiology using EEG (Garnsey et al, 1989), eye-tracking while reading paradigm (Traxler and Pickering, 1996), eyemovements in the visual world paradigm (Sussman and Sedivy, 2003), self-paced reading (Lee, 2004), among many others. There is also evidence that active dependency formation is crosslinguistically robust: Bangla (Chacón et al, 2016), Chamorro (Wagers et al, 2015), Dutch (Frazier and Flores d'Arcais, 1989), German (Schlesewsky et al, 2000), Italian (Vincenzi, 1991), Japanese (Aoshima et al, 2004), and Russian (Sekerina, 2003), to name a few. There is also evidence that it is robust in both neurotypical and aphasic populations (Dickey et al, 2007).…”
Section: Comprehenders Actively Construct Filler-gap Dependenciesmentioning
confidence: 99%
“…Psycholinguistic research with adults has provided much evidence for active dependency formation bias, i.e., incremental completion of the dependency at the earliest possible position (Aoshima, Phillips, & Weinberg, 2004;Chacón et al, 2016;Crain & Fodor, 1985;Frazier, 1987;Frazier & Clifton, 1989;Frazier & Flores D'Arcais, 1989;Garnsey, Tanenhaus, & Chapman, 1989;Johnson, Fiorentino, & Gabriele, 2016;McElree & Griffith, 1998;Omaki & Schulz, 2011;Parker, 2017;Pickering & Traxler, 2003;Staub, 2010;Stowe, 1986;Traxler & Pickering, 1996;Wagers, Borja, & Chung, 2015;Wagers & Pendleton, 2016). For example, an eye-tracking during reading study by Traxler and Pickering (1996) manipulated the Developing incrementality in filler-gap dependency 11 semantic fit of the filler and the verb (e.g., … the city/book that the author wrote about…), and found reading time increase at the verb region when the filler was an implausible object of the verb (city-wrote) compared to when it was a plausible object of the verb (book-wrote).…”
Section: Filler-gap Dependency Processing In Adultsmentioning
confidence: 99%